The health behaviours of young poles at the turn of XX and XXI century - Wołoszynek, Eliza; Oziemczuk, Karolina (Journal of Education, Health and Sport, 2018)
ABSTRACT Background. The increase of health-related knowledge and its accessibility, with the development of technology and social pressure on health care result in health gaining importance as a value. In the face of changes, one’s consciousness of the link between health behaviours and medical fitness is bigger and bigger. The young people in Poland are up-bringing in the domination of socio-ecological health model which highlights the entity’s lifestyle and its impact on health. Regular physical activity, appropriate, balanced nutrition, friendly interpersonal relationships, coping with stress and avoidance of risky behavior are the most important factors of the healthy human lifestyle. They affect the physical, mental, social development, health, learning and working ability. Objectives. The aim of this study was to analyse health behaviours among of Poles with reference to age, in recent years. Summary. The work in detail discusses biomedical paradigm of the health. Lifestyle concept as an effective way to prevent the occurrence of diseases, their development and complications were also described. Unfortunately, Poles are not aware of all the consequences of these threats. In connection with above, one should take care of systematic health education in the scope of effects reducing the negative impact on health threats.